PENGARUH PENGGUNAAN PEKTIN NABATI DENGAN PERSENTASE YANG BERBEDA TERHADAP WARNA DAN TEKSTUR YOGURT SUSU SAPI - Futra, Rayindatria Kusuma; Setyawardani, Triana; Astuti, Triana Yuni (ANGON: Journal of Animal Science and Technology, 2020)
Background. The research was conducted with the aim of knowing the use of vegetable pectin with different percentages of the color and texture of cow's milk yogurt sensoryly. Materials and methods. The material used is 5 liters of cow's milk cow milk from BBPTU-HPT Baturraden, Yogourmet dried yogurt starter, skim milk and 10 grams of vegetable pectin. The research method was an experiment with a randomized block design (RBD), with 4 treatments, with a total of 30 panelists. Results. The results showed that the use of pectin with different percentages in making cow's milk yogurt significantly affected the color of yogurt (P <0.01) and the texture of yogurt also had a very significant effect (P <0.01). The use of pectin with different percentages in the manufacture of cow's milk yogurt has a color average of P0: 0.58, P1: 0.40, P2: -0.406, P3: -049, P4: -0.35. The use of vegetable pectin with different percentages in making cow's milk yogurt has a mean texture of PO: -0.52, P1: 0.33, P2: -0.17, P3: 0.29, P4: 0.73. Conclusion. The use of pectin up to 0.8% in making yogurt increases the yellowish color and increasingly thick texture.